Experience Jesus. Really. : finding refuge, strength, and wonder through everyday encounters with God - Eldredge, John, 1960- (Nelson Books, 2025)
"New York Times bestselling author John Eldredge reveals the path of the 'ordinary mystic,' and invites readers into the refuge of experiencing deep, lasting, real communion with Jesus"--